UPAYA KOLABORATIF THE UNITED NATIONS OFFICE ON DRUGS AND CRIME (UNODC) DAN PEMERINTAH INDONESIA DALAM MENANGGULANGI HIV/AIDS DI INDONESIA - Liani, Jihan Nadra; Fadhilatunnisa, Dewi (Indonesian Association for International Relations, 2024)
This article aims to describe efforts to deal with HIV/AIDS in Indonesia through collaboration between The United Nations Office on Drugs and Crime (UNODC) and the Indonesian Government in the 2017-2020 Indonesia Country Program. The method used in this research is a qualitative method and literature study as a data collection technique. Meanwhile, international organization theory and the concept of Human Security are used as theoretical foundations. The results of this research indicate that efforts to control HIV/AIDS in Indonesia by the Indonesian Government in collaboration with UNODC are the right steps, considering that HIV/AIDS is a disease that has an impact on human health security. UNODC assists Indonesia in achieving its goals and interests through the Indonesia Country Program by designing a systematic work plan to discuss and contribute to the creation of a National Action Plan (RAN) to overcome the spread of HIV/AIDS among prisoners and convicts in Indonesia